Analysis Of Organoleptic Tests, Ph Tests, And Lactic Acid Levels In Saurkraut Fermentation From Cabbage (Brassica Oleracea) With The Addition Of Yellow Pears (Pyrus Nivalis) As An Antioxidant - Darvesh, Choirunnisa Ejaz; Afrilianti, Dinda; Fauziah, Fadilah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Cabbage (Brassica oleracea) is a vegetable that is rich in vitamins, fiber and minerals. Fermenting cabbage into sauerkraut is one solution to increase shelf life while producing functional food products. This research aims to analyze the characteristics of sauerkraut fermented from cabbage with the addition of yellow pears (Pyrus nivalis) as a source of natural antioxidants. The fermentation process is carried out naturally for five days with the addition of salt to support the growth of lactic acid bacteria (LAB). Evaluation of results is carried out through organoleptic tests (taste, aroma, texture), pH measurements to determine the acidity level, as well as analysis of lactic acid levels as an indicator of fermentation activity. The results showed that sauerkraut made from cabbage with the addition of yellow pear had good sensory characteristics, a pH value in the safe range for consumption, and lactic acid levels that were in accordance with fermented product standards. The addition of yellow pears is thought to contribute to the sensory quality and antioxidant compound content of the final product.